Relationship of brain derived neurotrophic factor DNA methylation with psychopathologic symptoms and antipsychotics in stable schizophrenia - Abd. Rahim, Nour El Huda; Rahim, Mohd Nabil Fikri; Ku Zaifah, Norsidah; Mohd Noor, Hanisah; Abdullah, Kartini; A.Talib, Norlelawati (2016)
Introduction: Brain derived neurotrophic factor (BDNF) contributes to dopamine neurotransmission by supporting the survival and differentiation of the neurons. During epigenetic event, methylated BDNF gene may cause reduction of its expression thus contribute to the clinical presentation and treatment response in Schizophrenia. Additionally, there are several confounding factors that may cause DNA methylation which include drug medication. The objective of our study is to quantitatively measure the DNA methylation level of BDNF and assess its relationship with psychopathological symptoms and antipsychotics. Methods: A total of 180 Schizophrenia cases were recruited from Psychiatry Clinic, Hospital Tengku Ampuan Afzan, Kuantan Pahang were studied. Total genomic DNA from subjects was subjected to Methylight Taqman analysis for quantitative measurement of BDNF gene DNA methylation. The psychopathological symptoms were assessed using Positive and Negative Syndrome Scale (PANSS). The treatment variables were gathered through the review of the medical records. Results: There were no correlation between the DNA methylation level of BDNF with subdomains of PANSS except for positive subdomain (r=0.04, p=0.03). There was significant difference of DNA methylation level of BDNF between the Risperidone treated group (1.310 ± 0.033%) and typical antipsychotic treated group (1.288 ± 0.043%) (p=0.013. Conclusions: The relationship between DNA methylation of BDNF with positive symptom might indicate BDNF DNA methylation role in the manifestation of Schizophrenia. Treatment with Risperidone increases DNA methylation of BDNF as compared to typical antipsychotics. Both of these conclusions require further evaluation.